ERK-mediated phosphorylation regulates SOX10 sumoylation and targets expression in mutant BRAF melanoma - Shujun Han (Nature Communications, 2018)
In BRAF mutant melanoma, inhibition of ERK1/2 induces FOXD3 and mediates RAF inhibitor resistance. Here, the authors show that ERK1/2 mediated phosphorylation regulates sumoylation of SOX10 which activates FOXD3, and depletion of SOX10 sensitises BRAF mutant melanoma cells to RAF inhibitors.